The Analysis of The Use of Social Media in Enhancing Students’ Speaking Skills - Mardiyah, Mutmainatul (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2025)
This study examines the behavior of students from the Faculty of Industrial Technology at Trisakti University in using social media platforms to improve their English-speaking skills. It investigates the frequency, purpose, and impact of social media on their learning process. A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data collection involved distributing questionnaires to 30 randomly selected respondents via Google Forms and conducting interviews. The collected data were processed according to research protocols and analyzed using multiple linear regression in SPSS 20. The results highlight key trends in student engagement, challenges encountered, and strategies for more effective use of social media for language learning. Factors such as frequency, purpose, accessibility, interactive learning, distractions, and limited feedback were found to significantly influence students’ use of social media to develop their English-speaking skills.